A Novel Competing Endogenous RNA Network Associated With the Pathogenesis of Graves’ Ophthalmopathy - Yue, Zifan; Mou, Pei; Chen, Sainan; Tong, Fei; Wei, Ruili (Frontiers in Genetics, 2021)
Background: Increasing evidence has recently revealed the roles of long noncoding (lncRNA)/circular RNA (circRNA)-microRNA (miRNA)-mRNA networks in multiple human diseases. However, a systematic lncRNA/circRNA-miRNA-mRNA network linked to Graves’ ophthalmopathy (GO) is still lacking. Materials and methods: The expression levels of RNAs in GO patients were measured through high-throughput sequencing technology, and the results were verified by quantitative real-time PCR (qRT-PCR). A protein-protein interaction (PPI) network was constructed using the Search Tool for the Retrieval of Interacting Genes (STRING) database, and hub genes were identified by the Cytoscape plug-in CytoHubba. Then, the miRNAs related to differentially expressed lncRNAs/circRNAs and mRNAs were predicted through seed sequence matching analysis. Correlation coefficient analysis was performed on the interesting RNAs for construction of a novel competing endogenous RNA (ceRNA) network. Results: In total, 361 mRNAs, 355 circRNAs, and 242 lncRNAs were differentially expressed in GO patients compared with control patients, 166 pairs were identified, and ceRNA networks were constructed. The qRT-PCR results showed that 4 mRNAs (THBS2, CHRM3, CXCL1, FPR2) and 2 lncRNAs (LINC01820:13, ENST00000499452) were differentially expressed between the GO patients and control patients. Conclusion: We constructed an innovative lncRNA/circRNA-miRNA-mRNA ceRNA network between the GO patients and control patients and identified two important ceRNA pathways, the LINC01820:13-hsa-miR-27b-3p-FPR2 ceRNA pathway and the ENST00000499452-hsa-miR-27a-3p-CXCL1 pathway, which probably affect the autoimmune response and inflammation in GO patients.